Islamic Religiusity In Serat Wedhatama Pupuh Gambuh - Rudi Permono Putro; Muhammad Rohmadi; Ani Rakhmawati (IBDA` : Jurnal Kajian Islam dan Budaya, 2021)
Javanese society was awarded a noble cultural heritage. Every Javanese tradition and literature always contains the teachings of the value of goodness in it, including Serat Wedhatama pupuh Gambuh by KGPAA Mangkunegara IV. Serat Wedhatama pupuh Gambuh contains the value of Islamic religiosity, which is very important to be studied considering the occurrence of moral degradation among generations of the nation. Weak religious values are one of the factors in this moral degradation. So that this study is important to do with the hope that it can contribute to the cultivation of religious and cultural values to the nation's generation. The results of this study indicate that there is a value of Islamic religiosity in Serat Wedhatama pupuh Gambuh. These values can be used as parameters and guidelines for life. This study can also be used as a solution to answer the condition of the people who are in the midst of deculturation and dereligiosity.